Use of floating materials for evaporation control in the semi-arid tropic - Porto, Everaldo Rocha; Amorim Neto, Malaquias da Silva; Silva, Daniel Delfino da (Pesquisa Agropecuaria Brasileira, 2014)
Floating materials were tested in Class A evaporation pans for reducing evaporation tosses from free water surfaces. The covering materials consisted of impermeable disks of vermiculite covered with parafine and palm (Copernicia cerifera Mart.) wax; vitrified clay spheric balls; clay spheric balls without vitrification; and styrofoam disks rendered impermeable by a mixture of palm wax and melted parafine. Each of these treatments covered 80% of the exposed surface of the evaporation pan and controlled 54%, 60%, 50% e 61% of evaporation losses, respectively. These results clearly show that all these covers are viable in controlling evaporation losses.